Mechanistic study on the nuclear modifier gene MSS1 mutation suppressing neomycin sensitivity of the mitochondrial 15S rRNA C1477G mutation in Saccharomyces cerevisiae. - Qiyin Zhou; Wei Wang; Xiangyu He; Xiaoyu Zhu; Yaoyao Shen; Zhe Yu; Xuexiang Wang; Xuchen Qi; Xuan Zhang; Mingjie Fan; Yu Dai; Shuxu Yang; et al. (PLoS ONE)
The phenotypic manifestation of mitochondrial DNA (mtDNA) mutations can be modulated by nuclear genes and environmental factors. However, neither the interaction among these factors nor their underlying mechanisms are well understood. The yeast Saccharomyces cerevisiae mtDNA 15S rRNA C1477G mutation (PR) corresponds to the human 12S rRNA A1555G mutation. Here we report that a nuclear modifier gene mss1 mutation suppresses the neomycin-sensitivity phenotype of a yeast C1477G mutant in fermentable YPD medium. Functional assays show that the mitochondrial function of the yeast C1477G mutant was impaired severely in YPD medium with neomycin. Moreover, the mss1 mutation led to a significant increase in the steady-state level of HAP5 (heme activated protein), which greatly up-regulated the expression of glycolytic transcription factors RAP1, GCR1, and GCR2 and thus stimulated glycolysis. Furthermore, the high expression of the key glycolytic enzyme genes HXK2, PFK1 and PYK1 indicated that enhanced glycolysis not only compensated for the ATP reduction from oxidative phosphorylation (OXPHOS) in mitochondria, but also ensured the growth of the mss1(PR) mutant in YPD medium with neomycin. This study advances our understanding of the phenotypic manifestation of mtDNA mutations.